Examination on the Denoising Methods for Electrical and Acoustic Emission Partial Discharge Signals in Oil - Ahmad Hafiz Mohd Hashim; Norhafiz Azis; Jasronita Jasni; Mohd Amran Mohd Radzi; Masahiro Kozako; Mohamad Kamarol Mohd Jamil; Zaini Yaakub (IAES Indonesian Section, 2023)
Partial discharge (PD) measurements either through electrical or acousticÂ emission approaches can be subjected to noises that arise from differentÂ sources. In this study, the examination on the denoising methods forÂ electrical and acoustic emission PD signal is carried out. The PD wasÂ produced through needle-plane electrodes configuration. Once the voltageÂ reached to 30 kV, the electrical and acoustic emission PD signals wereÂ recorded and additive white Gaussian noise (AWGN) was introduced. TheseÂ signals were then denoised using moving average (MA), finite impulseÂ response (FIR) low/high-pass filters, and discrete wavelet transform (DWT)Â methods. The denoising methods were evaluated through ratio to noise levelÂ (RNL), normalized root mean square error (NRMSE) and normalizedÂ correlation coefficient (NCC). In addition, the computation times for allÂ denoising methods were also recorded. Based on RNL, NRMSE and NCCÂ indexes, the performances of the denoising methods were analyzed throughÂ normalization based on the coefficient of variation (ð¶ð‘£). Based on the currentÂ study, it is found that DWT performs well to denoise the electrical PD signalÂ based on the RNL and NRMSE ð¶ð‘£ index while MA has a good denoisingÂ NCC and computation time ð¶ð‘£ index for acoustic emission PD signal.